PENERAPAN METODE ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS IV SD NEGERI 019 BONAN DOLOK - Putri Marwah; Parulian Siregar; Junita Irawati (EDU RESEARCH, 2025)
This research aims to improve student learning outcomes in Indonesian Language Learning Materials for Pekerjaan di Sekitarku. This research was carried out at SD N 019 Bonan Dolok. The research method used is classroom action research with a research design by Kemmis and Mc Taggart. Sampling was carried out using total sampling technique. The research sample consisted of 35 students. Data analysis in this research uses qualitative analysis and quantitative analysis. The average learning outcome for pre-cycle students was 35.4, the learning outcome for cycle I students was 65.7 and the learning outcome for cycle II students was 78. Furthermore, the percentage of completion for pre-cycle students was 14.3%. , the percentage of student completion was 48.6% and the percentage of student completion in cycle II increased by 37.1 from cycle I, namely 85.7%. This shows that there is an influence of the application of the Role Playing Method on the Indonesian language learning outcomes of Pekerjaan di Sekitarku students at SD N 019 Bonan Dolok.